Spiradenocarcinoma: A Comprehensive Data Review. (October 2017) - Staiger, Roxane D.; Helmchen, Birgit; Papet, Claudia; Mattiello, Diana; Zingg, Urs
Abstract : Introduction: Spiradenocarcinomas (SCs) are rare and potentially aggressive skin adnexal tumors. Optimal treatment has not yet been established. Experiences with this carcinoma are mostly presented in case reports and few case series. Objective: To generate to a synopsis of published data on SC with regard to diagnostic procedures, treatment, and outcome. Results: Median patient age was 60 years and sex distribution was balanced. Tumor manifestations were evenly distributed within the sweat gland carrying skin. The most commonly reported symptom was accelerated growth of a longstanding indolent lesion, typically present for more than 2 years. Metastatic spread to the lung, bone, lymph nodes, liver, kidney, and breast has been documented. For staging computed tomography (CT) and positron emission tomography-CT are recommended, especially for detection of hematogenic metastases and lymph node involvement. Clear resection margins and tumor free regional lymph nodes reduce recurrence and carcinoma related death. Although low-grade SCs were reported over 3 times more often, high-grade carcinomas show a greater likelihood for recurrence and lethal outcome. Conclusion: Suspicion of an SC should lead to performance of a magnetic resonance imaging for defining tumor extent, and a fludeoxyglucose positron emission tomography-CT for detection of metastases. Radical tumor excision and resection of tumor involved regional lymph nodes are essential for a curative approach. Histopathological evaluation should involve determination of tumor differentiation grade, because high-grade carcinomas seem to have a much more aggressive behavior. Excision of distant metastases has no therapeutic value. Follow-up needs to be carried out in short intervals with frequent imaging.